A study to determine human-related errors at the level of top management, safety supervisors & workers during the implementation of safety practices in the construction industry. (June 2023) - Nazeer Ahamed, M.F.; Mariappan, M.
Highlights: The present study has made significant additions to the existing knowledge of literatures related to the occurrence of human-related errors by identifying 140 contributing errors behind the occurrence of three major issues such as lack of supply & usage of PPE, improper safety training, poor safety supervision at the level of Top Management (TM), Safety Supervisors (SS) & Workers(W) through in-depth focus interview. The findings of this study will enable the top management, Safety supervisors & workers of the construction organizations to get to know about the errors that occur at their levels. Through this, they can contribute to the prevention of accidents by avoiding such issues at their levels while implementing safety practices such as the supply & usage of PPEs, Safety Training and Safety Supervision. Abstract: The safety performance of the Indian construction industry is not satisfactory, due to which many accidents are still prevailing in the construction industry. To execute the project successfully without any accidents all the levels of employees must be consciously involved in preventing accidents without committing errors at their individual level. Many researchers have conducted studies to find out the major issues that lead to causes of accidents at single employee level. Finding out major issues at single employee level alone may not be sufficient to prevent accidents, because construction is not a domain of a single category of employees; instead, it is a field of several categories of employees working at various levels in the execution of the projects. Any single error committed at any of the employee level may contribute to major issues that would leads to accidents. Therefore, in order to identify the potential errors that occur at multi-level employees, the present study has adopted three-dimensional view strategy to investigate human related errors that occur during the implementation of each stage of safety practices such as supply & usage of Personal Protective Equipment (PPE), Safety training (ST) and Safety supervision (SSV) from Top management (TM), Safety supervisors (SS) and workers (W) perspectives. This study has identified three major issues such as lack of supply & usage of PPE, improper safety training, poor safety supervision and 140 contributing errors (responses) behind the occurrence of these three major issues through focus interviews carried out at construction organizations based in Chennai city, South India. Out of identified 140 contributing errors, 45 contributing errors were behind the occurrence of lack of supply & usage of PPE (TM level −26 errors; SS level-13 errors; W level −6 errors), 32 contributing errors were behind the occurrence of improper safety training (TM level-18 errors; SS-12 errors; W level-2 errors) and 63 contributing errors were behind the occurrence of poor safety supervision (TM level-32 errors; SS level −21 errors; W level −10 errors). The results obtained are explained figuratively by comparing it with the results of similar previous studies. The study results shows that any major issue that lead to cause of accidents possibly cannot occur alone, but would occur as a result of several contributing errors from various levels of employees. The findings of the study may be helpful for the construction organizations to prevent accidents in future by avoiding the identified contributing errors at the levels of TM, SS, and W.